(3GdMTGFTs - (3OjSbhQjOS GdYjf RQHjs ((3eMeO Hf YHOGdedc Hf jMji s)
(3ChdgG (B:s
(3cKjQ ef GdbOeGA hGdPjf HYOge hVYhG cJHkG aj JQcjH GdCOhjI hai bhGgG hai HfGFgG eG GTJbJ Gf GXgQ dc Gf MQcJi ajeG bUOJ dg ef gPG Gdaf ef GdYde djSJ HMQcI HGWdI s
(3BNQgG (B:s
(3hjSbi CjVkG ef YUGQI GdNTNGT (B: (3agPG YdGL GdOhGH PGJ GdSehe s
(3GdebGdJGf GdSGOSI hGdSGHYIs
(3GfXQ agQS GdWH HQbe (B90 (3cJGH GdMTGFTs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B82 s
Keywords: (3GdWHs